BOOK REVIEW: Silvia Marton, „«Republica de la Ploiești» și începuturile parlamentarismului în România” [“‘Ploiești Republic’ and the beginning of the parlamentarism in Romania”], București, Humanitas, 2016, 307 p., ISBN: 978-973-50-5160-0 - LUTZ, Diana Georgiana (Studia Universitatis Babeș-Bolyai Historia, 2018)
Tracing its origins back to ancient times, the republic, as a form of government, remerged once again in Renaissance, although its modern form developed notably only after the French Revolution, whose ideas played an essential role in the construction of the modern states. Being seen as the older “sister” of Romania, due to their common Latin roots, France played the role of an influencer in the transformation of the two Principalities of Moldova and Walachia in the united and autonomous and then independent state of Romania. Although during the second half of the nineteenth century France and Romania followed different ways in what concerns the form of government, the first – an empire and, then republic, and the second – principality and, then monarchy, the idea of republic, borrowed from the French political culture, started to be promoted as a solution to the crises that the principality on the Danube was facing around 1870. The breaking point of this was the proclamation of the “Ploiești Republic” (August 8, 1870), launched by the radical-liberal political faction of the time. Despite being no more than a failed and ridiculous attempt of regime change, its symbolic meaning in the process of modernization of Romania remain undeniable, fully justifying the research proposed by Silvia Marton in her new book, in which she emphasises the roots, the unfolding and the consequences of this hazardous political venture.